2014
DOI: 10.21307/ijssis-2017-657
|View full text |Cite
|
Sign up to set email alerts
|

Self-Tuning Fuzzy Speed Controller Of Travelling Wave Ultrasonic Motor

Abstract: Aiming at the nonlinear characteristic of ultrasonic motor, some control strategies have been proposed to control the rotating speed of ultrasonic motor. But most of these strategies are too complex to realize using a low-cost embedded device. In this paper, a simple fuzzy speed controller is designed for ultrasonic motor. Until now, there has no mature and theoretic design method of fuzzy controller. Therefore, experience of expert is often used as the base of design. It makes the design of fuzzy controller b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…This study suggests the suggested approach to handle the large-size TSP routing system. There are some extended traveling salesman problems applications in [18][19][20][21][22]. An effective revisiting algorithm for simultaneous localization and mapping using landmarks is presented by Hyejeong Ryu [23] to choose positions to revisit by taking into account both landmark visibility and sensor measurement uncertainty in TSP.…”
Section: Methodsmentioning
confidence: 99%
“…This study suggests the suggested approach to handle the large-size TSP routing system. There are some extended traveling salesman problems applications in [18][19][20][21][22]. An effective revisiting algorithm for simultaneous localization and mapping using landmarks is presented by Hyejeong Ryu [23] to choose positions to revisit by taking into account both landmark visibility and sensor measurement uncertainty in TSP.…”
Section: Methodsmentioning
confidence: 99%